Ag nanoparticles decorated ion-beam-assisted TiO2 thin films for tuning the water splitting activity from UV to visible light harvesting. Issue 15 (15th October 2017) - Sreedhar, Adem; Sreekanth, T.V.M.; Kwon, Jin Hyuk; Yi, Jonghoon; Sohn, Youngku; Gwag, Jin Seog
Abstract: In this study, tuning of the photoelectrochemical (PEC) water splitting activity from UV to visible region was achieved on RF magnetron sputtered TiO2 thin films grown under various Ar ion-beam energies (0, 60 and 110 eV). We propose a new strategy of energetic Ar ion-beam projection towards the substrate surface during the film growth. The resulting TiO2 films were decorated with silver (Ag) nanoparticles for efficient plasmon-enhanced PEC water splitting activity under visible light illumination. Firstly, the ion-beam-energy induced a well-defined anatase TiO2 (101) phase with improved crystallinity, which is key factor responsible for the enhanced PEC activity. Interestingly, XPS studies revealed the presence of Ti 3+ states along with the Ti 4+ ones, which sensitively influence the UV and visible light absorption. Furthermore, AFM images revealed rough surface topography of the films, which is highly desirable for large area exposure to the electrolyte. In addition, the UV–vis transmittance spectra showed a stronger red shift in the optical absorption edge and a reduced band gap, which are crucial factors for charge carrier generation. Studies on Ag nanoparticles decorated TiO2 films show that, due to the transfer of surface plasmon energy from the Ag nanoparticles to TiO2, efficient visible light water splitting activity was achieved. This is about five times higher than that observed for TiO2 films under UV light. Comprehensively, this novel approach could pave the way for efficient visible-light-driven PEC water splitting activity.